Development of a Phytomelatonin-Rich Extract from Cultured Plants with Excellent Biochemical and Functional Properties as an Alternative to Synthetic Melatonin - Francisca Pérez-Llamas; Josefa Hernández-Ruiz; Alberto Cuesta; Salvador Zamora; Marino B. Arnao (MDPI AG, 2020)
Melatonin is a pleiotropic molecule with multiple and various functions. In recent years, there has been a considerable increase in the consumption of melatonin supplements for reasons other than those related with sleep (as an antioxidant, for anti-aging, and as a hunger regulator). Although the chemical synthesis of melatonin has recently been improved, several unwanted by-products of the chemical reactions involved occur as contaminants. Phytomelatonin, melatonin of plant origin, was discovered in several plants in 1995, and the possibility of using raw plant material as a source to obtain dietary supplements rich in phytomelatonin instead of synthetic melatonin, with its corresponding chemical by-products was raised. This work characterizes the phytomelatonin-rich extract obtained from selected plant material and determines the contents in phytomelatonin, phenols, flavonoids, and carotenoids. Additionally, the antioxidant activity was measured. Finally, a melatonin-specific bioassay in fish was carried out to demonstrate the excellent biological properties of the natural phytomelatonin-rich extract obtained.